MUSEOLOGIAL ACTION’S MAIN FIELDS (Cadernos de Sociomuseologia, 2009)
Museology has emerged and has been organised as a field of knowledge, precisely to frame the technical, theoretical and methodological aspects, regarding the constitution, implementation and evaluation of the processes that societies establish for the selection, treatment and extroversion of the memory indicators, transforming them into patrimonial references and projecting them into the constitutive fields of cultural heritage. It is therefore, one of the areas of knowledge that deals with the framing of heritage and their professionals are agents of memory education. The constitution of the parameters that define and delimit the museological action field has been outlined in the course of the centuries, if we consider the technical efforts related to the identification and organisation of collections, in addition to the curatorial treatment of specimens from nature, of objects, of the intangible heritage registers. The same length of elaboration is true if we evaluate the communication initiatives and of education of the senses.